Modeling of TiN coating thickness using RSM approach - Mohamad Jaya, Abdul Syukor; Mohd Hashim, Siti Zaiton; Haron, Habibollah; Muhamad, Mohd Razali; Hasan Basari, Abd Samad; Abd. Rahman, Md. Nizam (Trans tech Publication, Switzerland, 2014)
In this paper, modeling of Titanium Nitrite (TiN) coating thickness using Response Surface Method (RSM) is implemented. Insert cutting tools were coated with TiN using Physical Vapor Deposition (PVD) sputtering process. N2 pressure, Argon pressure and turntable speed were selected as process variables while the coating thickness as output response. The coating thickness as an important coating characteristic was measured using surface profilometer equipment. Analysis of variance (ANOVA) was used to determine the significant factors influencing TiN coating thickness. Then, a polynomial linear model represented the process variables and coating thickness was developed. The result indicated that the actual validation data fell within the 90% prediction interval (PI) and the percentage of the residual errors were low. Findings from this study suggested that Argon pressure, N2 pressure and turntable speed influenced the TiN coating thickness.